Assessment of Circulating Protein Signatures for Kidney Transplantation in Pediatric Recipients - Sigdel, Tara K.; Sarwal, Minnie M. (Frontiers in Medicine, 2017)
Identification and use of non-invasive biomarkers for kidney transplantation monitoring is an unmet need. A total of 121 biobanked sera collected from 111 unique kidney transplant patients (children and young adults, ≤19 yrs) and 10 age-matched healthy normal controls were used to profile serum proteins using semi-quantitative proteomics. The proteomics data was analyzed to identify panels of serum proteins that were specific to various transplant injuries which included acute rejection (AR), BK virus nephropathy (BKVN), and chronic allograft nephropathy (CAN). Gene expression data from matching peripheral blood mononuclear cells (PBMCs) was interrogated to investigate association in between soluble serum proteins and altered gene expression of corresponding genes in different injury phenotypes. Analysis of the proteomics data identified from different patient phenotypes, with a criteria of FDR <0.05 and at least 2-fold changes in either direction, resulted in a list of 10 proteins that distinguished kidney transplant injury from no-injury. Similar analyses to identify proteins specific to chronic injury, acute injury, and acute rejection after kidney transplantation identified 22, 6, and 10 proteins respectively. Elastic Net logistic regression method was applied on the 137 serum proteins to classify different transplant injuries. This algorithm has identified panels of 10-serum proteins specific for AR, BKVN, and CAN with classification rates 93%, 93%, and 95% respectively. The identified proteins could prove to be potential surrogate biomarkers for routine monitoring of injury status of pediatric kidney transplant patients.